2020
DOI: 10.1002/gj.3818
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of modern tectonic stress fields in the north‐eastern margin of Tibetan Plateau

Abstract: A modern tectonic stress field for the northeastern margin of Tibetan Plateau was determined using linear inversion. Focal mechanism solutions and the depths of 54 earthquakes from 2009 to 2017 were obtained from broadband seismic waveforms. We derived the tectonic stress field using the SATSI (Spatial and Temporal Stress Inversion) software based on the damped linear inversion method. The stress tensor structures are primarily indicative of strike-slip and thrust faulting; their distributions are controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…The dominant depth range of seismic activities in the study area is 5-15 km, with a few events at depths up to 20 km (L. Li et al, 2020;. As mentioned in the introduction, seismic activities are closely related to fault activities.…”
Section: Fault Slip Rates Of the Main Faultsmentioning
confidence: 90%
“…The dominant depth range of seismic activities in the study area is 5-15 km, with a few events at depths up to 20 km (L. Li et al, 2020;. As mentioned in the introduction, seismic activities are closely related to fault activities.…”
Section: Fault Slip Rates Of the Main Faultsmentioning
confidence: 90%
“…The dominant depth range of seismic activities in the study area is 5-15 km, with a few events at depths up to 20 km (Li et al, 2020). Therefore, we extracted the kinematic characteristics up to a depth of 20 km for the main faults of the study area using our 3D geomechanics model.…”
Section: Fault Slip Rates Of the Main Faults 200mentioning
confidence: 99%
“…It has been estimated that 1400 years have elapsed since its last activation (Xue, 2014). 360 (Gan et al, 2002); L1 is the length of the fault (Xu et al, 2016); L2 is the width of the fault, measured at the dominant focal depth of the region (Li et al, 2020); μ is the shear modulus of the rocks (Aki et al, 2002); t is the time that has elapsed since the most recent earthquake (Gan et al, 2002;Shi et al, 2013Shi et al, , 2014Wang et al, 2001); S is the largest maximum coseismic slip, calculated using the method of Gan et al (2002); Ms is the earthquake magnitude corresponding to the energy accumulated by the fault between recurrences (Purcaru et al, 1978); T is the recurrence interval of the fault, where T = S/(V1-V2) (Shen et al, 2009). The fault names are defined in Figure 1 and Figure 14.…”
Section: Seismic Gap At the Southern Liupanshan And Guguan-baoji Faultsmentioning
confidence: 99%
“…Li , Rao, Qiu, He and Gao (2020) integrated the observed focal mechanism solutions since 1976, the velocity vectors of 25 years of GPS measurements, and the results of existing field studies on active structures in the eastern Tian Shan, to demonstrate that slip partitioning under oblique convergence is the main characteristic of active deformation. Meanwhile, they suggested that constraints on intermontane structures are still needed in future investigations for better constraining the strain distribution in the eastern Tian Shan.…”
Section: Late Cenozoic Intracontinental Deformationmentioning
confidence: 99%